2020
DOI: 10.31235/osf.io/ueds4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“No Central Stage”: Telegram-based activity during the 2019 protests in Hong Kong

Abstract: We examine Telegram-based activities related to the 2019 protests in Hong Kong thus presenting the first study of a large Telegram-aided protest movement. We contribute to both - scholarship on Hong Kongese protests and research on social media-based protest mobilization. For that, we rely on the data collected through Telegram’s API and a combination of network analysis and computational text analysis. We find that the Telegram-based network was cohesive ensuring the efficient spread of protest-related inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Previous research in Telegram-centred anti-government movements has focused on more restrictive and authoritarian contexts (Akbari and Gabdulhakov, 2019; Bykov et al, 2021; Urman et al, 2020; Wijermars and Lokot, 2022), stressing moderation modes, censorship escape and alternative media, marking the messenger a useful tool for different types of movements. The results of this study show how Telegram is employed as a space that unifies secluded, separate, deplatformed communities sharing similar discourse and narratives.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in Telegram-centred anti-government movements has focused on more restrictive and authoritarian contexts (Akbari and Gabdulhakov, 2019; Bykov et al, 2021; Urman et al, 2020; Wijermars and Lokot, 2022), stressing moderation modes, censorship escape and alternative media, marking the messenger a useful tool for different types of movements. The results of this study show how Telegram is employed as a space that unifies secluded, separate, deplatformed communities sharing similar discourse and narratives.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative research or research examining a specific platform is relatively scarce: Valenzuela et al (2018) showed that when organising protest action, Facebook is used for communication with strong ties, while Twitter is used to influence weak ties; Ahuja et al (2018) found that affordances of a SM platform can predict the success of CA, depending on its objectives. Papers discussing Telegram and CA are rare and explore mostly its use in political protests: e.g., Hong Kong 2019 protests (Urman, Chun-ting Ho and Katze, 2020), Belarus 2020 protests (Wijermars and Lokot, 2022).…”
Section: Technology Affordancesmentioning
confidence: 99%
“…In addition to Twitter and Facebook, the role of which have been more widely studied (Khamis et al (2012), Metzger and Siegel (2019)), we extend analysis to include data from Telegram "an encrypted platform that is harder for governments to monitor" (Mitts (2019)). Much of the research on Telegram has focused on its use by ISIS (Prucha (2016), McDowell-Smith et al (2017), Yayla and Speckhard (2017)), though Telegram's privacy policies also support civilians and protest movements worldwide (Urman et al (2020)). Though much work has been dedicated to the role of social media in constructing violence narratives, it also plays a vital role in migration movement (Frouws et al (2016), Miconi (2020), Sánchez-Querubín and Rogers ( 2018)).…”
Section: Social Media and Information Accessmentioning
confidence: 99%